Corruption, nonperforming loans, and economic growth: International evidence - Tran Hung Son (Taylor & Francis Group, 2020)
This paper explores the impact of corruption on both the banking sector and economic growth; we determine the impact using aggregate data from the World Bank covering 120 countries over the period 2004–2017. The results of 3SLS regressions show that the relationship between corruption and the ratio of nonperforming loans was positive, thus deteriorating the soundness of the banking system. In this study, we also find evidence that banking system is a channel that transfers the impact of corruption on economic growth: Corruption leads to higher levels of nonperforming loans in the banking sector; as a result, it decreases economic growth. The findings survive a battery of robustness tests, including alternative corruption measurement and System Generalized Method of Moments regression for dynamic models with an interaction term.